2008
DOI: 10.1002/ase.55
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interactive, computerized educational modules on preclinical medical education

Abstract: Interactive computerized modules have been linked to improved retention of material in clinical medicine. This study examined the effects of a new series of interactive learning modules for preclinical medical education, specifically in the areas of quiz performance, perceived difficulty of concepts, study time, and perceived stress level. We randomly allocated 102 medical student volunteers into control and experimental groups. All participants studied selected anatomical and physiologic concepts using existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 10 publications
(10 reference statements)
2
51
1
Order By: Relevance
“…Kembera et al 2010) that the quality of communication in an online environment may be more important than access to information alone however. The discrepancy with other studies which found no differences between the blended learning and face-to-face approaches in terms of their impact on students' achievement (Kennedy & McCallister, 2000;O'Leary, 2008;Banks, 2004;Alshwiah, 2009;Bryner et al, 2008;Utts et al, 2003) needs to be explained or indicates areas for further research. This small-scale study has, of course, limited inference and some systematic variation may result from the limited randomisation at class level.…”
Section: E-learning and Face-to-face Approachescontrasting
confidence: 81%
See 1 more Smart Citation
“…Kembera et al 2010) that the quality of communication in an online environment may be more important than access to information alone however. The discrepancy with other studies which found no differences between the blended learning and face-to-face approaches in terms of their impact on students' achievement (Kennedy & McCallister, 2000;O'Leary, 2008;Banks, 2004;Alshwiah, 2009;Bryner et al, 2008;Utts et al, 2003) needs to be explained or indicates areas for further research. This small-scale study has, of course, limited inference and some systematic variation may result from the limited randomisation at class level.…”
Section: E-learning and Face-to-face Approachescontrasting
confidence: 81%
“…Moreover, further recent studies (Utts Sommer, Acredolo, Maher & Matthews, 2003;Taradi, Taradi, Radic & Pokrajac , 2005;Akkoyunlu & Soylu, 2006;Scida & Saury, 2006, Pereira et al, 2007Bryner, Saddawi-Konefka & Gest 2008), McFarlin, 2008O'Leary, 2008;Alshwiah, 2009;and Gurpinar, Zayim, Ozenci, & Alimoglu, 2009) have compared blended learning (which combines elements of e-learning and face-toface instruction) with face-to-face classroom learning. A comprehensive analysis of the variation in impact is described by Bernard et al (2009).…”
Section: Definitions Of E-learningmentioning
confidence: 99%
“…Multiple reports compare problem-based learning (Azer and Eizenberg, 2007), peer teaching (Krych et al, 2005;Evans and Cuffe, 2009), team-based learning (Nieder et al, 2005), computer or web-based teaching materials (Bryner et al, 2008;Petersson et al, 2009), and clinical skills (Dusseau et al, 2008) with traditional dissection methodology. Winkelmann (2007) reviewed several novel teaching methods and found that they were mostly judged to be ''not disadvantageous'' while at the same time not achieving significantly better results than traditional teaching methods on comparable examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Computer technology has become an increasingly important educational resource, which has dramatically changed teaching and learning in the medical curriculum (Chodorow, 1996;Clark, 2002;Ruiz et al, 2006;Bryner et al, 2008). This adoption of technology into the classroom was accelerated with expansion of the Web, which elevated the level of innovation and collaboration in the development of educational applications by making it easier for faculty to author, distribute and update courseware (Candler and Blair, 1998;McNulty et al, 2000;Levine, 2002;Nieder and Nagy, 2002).…”
Section: Introductionmentioning
confidence: 99%